Ð Ð¾Ð»ÑŒ Ð¾Ð±Ñ‰ÐµÐ³Ð¾ ÑƒÐ¼ÐµÑ€ÐµÐ½Ð½Ð¾Ð³Ð¾ Ð¾Ñ…Ð»Ð°Ð¶Ð´ÐµÐ½Ð¸Ñ Ð² Ð¾Ð±ÑƒÑ‡ÐµÐ½Ð¸Ð¸ Ð¶Ð¸Ð²Ð¾Ñ‚Ð½Ñ‹Ñ… Ñ Ñ€Ð°Ð·Ð½Ñ‹Ð¼ Ñ‚Ð¸Ð¿Ð¾Ð¼ Ð²Ð¾Ð·Ð±ÑƒÐ´Ð¸Ð¼Ð¾ÑÑ‚Ð¸ Ð½ÐµÑ€Ð²Ð½Ð¾Ð¹ ÑÐ¸ÑÑ‚ÐµÐ¼Ñ‹ - Nikishkova, I. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The results of studying the possibility of a modulating effect of an organism’s general moderate cooling on the learning process course in the model of active avoidance behaviour (AAB) formation in animals of different age are shown. The results of the work allow to consider a preliminary general moderate cooling as a contributing to more successful AAB formation and preventing the adaptive behaviour pathologies, occurring in animals. The age peculiarities of this cooling effect are demonstrated as well.